Design and Statistical Optimization of Novel Polyelectrolyte Complex Microbeads to Improve Entrapment Efficiency and Release Study of Vildagliptin - Tiwari, Ritesh K.; Singh, Lalit; Singh, Mukesh Kr. (Recent Advances in Drug Delivery and Formulation, 2023)
Background: The current research focused on the improvement of drug entrapment efficiency and release study of hydrophilic drug through polymer complextation. Objective: Ionotropic gelation technique was utilised for the preparation of Polyelectrolyte complex microbeads of Vildagliptin using Sodium alginate and Eudragit RL100 and their performance was optimized by Central composite design. Methods: Fourier Transform Infrared Spectroscopy, Scanning Electron Microscope, Differential Scanning Calorimetry, particle size, Drug Entrapment Efficiency, X-ray diffraction and in vitro drug release at 10hr were chosen for evaluating formulated microbeads. The impact of independent variables like concentration of sodium alginate and eudragit RL100 was examined over dependent responses. Results: The interpretation of XRD, SEM, DSC, and FTIR affirmed no drug excipients interference and confirmed formation of polyelectrolyte complex microbeads. For complex microbeads, the maximum and minimum drug release after 10 hours was obtained as 96.23.5% and 89.45%, respectively. The 32 central composite design was further used to obtain response surface graph and the values for the particle size, DEE and Drug release were retained as 0.197, 76.30 % and 92.15%, respectively for the optimize batch. Conclusion: The result suggested the combination of two polymers (Sodium alginate and Eudragit RL100) were suitable for improving the entrapment efficiency of hydrophilic drug (Vildagliptin). The central composite design (CCD) technique is an effective tool for obtaining optimal drug delivery systems of Vildagliptin polyelectrolyte complex microbeads.
Keywords: HbA1C